PEMANTAUAN STATUS GIZI BALITA DAN ANAK USIA SEKOLAH SERTA EDUKASI PHBS DI DESA NYOGAN KAB. MUARO JAMBI - Ummi Kalsum; Hendra Dhermawan Sitanggang; Evy Wisudariani (Universitas Jambi, 2021)
ABSTRACT The nutritional problems of toddlers and children in the Anak Dalam Tribe are malnutrition and stunting. One of the factors is the lack of a sanitary and healthy living behavior in the community. The condition of environmental health and environmental sanitation that meets the requirements is only 50%, the decline in the behavior of mothers in monitoring the growth and development of children at the Posyandu and monitoring of nutritional status in schools tends not to be carried out. It is necessary to educate the public regarding sanitary and healthy living behavior and monitoring the nutritional status of toddlers and school-age children in Nyogan Village. Community service activities are carried out through counseling activities for school children at SDN 238 and training for toddlers and stunting cadres in Nyogan Village. The results of the activity showed a significant increase in students' knowledge with an average increase of 6.31 points. In the training of cadres, it was also found that there was an increase in cadre knowledge, the average knowledge during the pre-test was 15.63 and increased to 16.25 during the post-test. It is also seen that there is an increase in the skills of cadres in anthropometric measurements which is shown through practical activities in measurement simulations. All the participants of the activity looked enthusiastic and showed seriousness in participating until the end of the event. The results of monitoring nutritional status according to the Body Mass Index according to Age (BMI/U) of students who experience malnutrition are still high, reaching 35.8% and 9% being overweight and obese. This activity is expected so that students and families can apply sanitary and healthy living behaviors, both at school and at home, and the school can monitor the nutritional status on a regular basis for toddlers and school-age children both at Posyandu and in screening activities for school children through the program. UKS. Keywords: Nutritional Status, Sanitary living culture, Monitoring of Nutritional Status, Education, SAD, KAT ABSTRAK Masalah gizi balita dan anak pada Suku Anak Dalam yaitu gizi kurang dan pendek. Salah satu faktornya adalah belum membudayanya perilaku hidup bersih dan sehat di masyarakat. Kondisi kesehatan lingkungan dan sanitasi lingkungan yang memenuhi syarat hanya 50%, menurunnya perilaku ibu dalam memantau tumbuh kembang anak di Posyandu serta pemantauan status gizi di sekolah cenderung tidak dilakukan. Perlu edukasi kepada masyarakat terkait perilaku hidup bersih dan sehat serta pemantauan status gizi balita dan anak usia sekolah di Desa Nyogan. Kegiatan Pengabdian kepada masyarakat dilaksanakan melalui kegiatan penyuluhan kepada anak sekolah SDN 238 dan pelatihan kader posyandu balita dan kader stunting di Desa Nyogan. Hasil kegiatan menunjukkan adanya peningkatan pengetahuan siswa secara signifikan dengan rata-rata peningkatan sebesar 6,31 poin. Pada pelatihan kader juga diperoleh adanya peningkatan pengetahuan kader, rata-rata pengetahuan saat pre-test 15,63 dan meningkat menjadi 16,25 saat post test. Juga terlihat ada peningkatan keterampilan kader dalam pengukuran antropometri yang ditunjukkan melalui kegiatan praktik pada simulasi pengukuran. Seluruh peserta kegiatan terlihat bersemangat dan memperlihatkan keseriusan dalam mengikuti hingga selesai acara. Hasil pemantauan status gizi menurut Indeks Massa Tubuh menurut Umur (IMT/U) siswa yang mengalami gizi kurang masih tinggi yaitu mencapai 35,8% dan 9% berstatus Gizi lebih dan obesitas. Kegiatan ini diharapkan agar siswa dan juga keluarga dapat menerapkan perilaku hidup bersih dan sehat, baik di sekolah maupun di rumah, serta pihak Sekolah dapat melakukan pemantauan status gizi secara rutin pada balita dan anak usia sekolah baik di Posyandu maupun dalam kegiatan penjaringan anak sekolah melalui program UKS. Kata Kunci : Status Gizi, PHBS, Pemantauan Status Gizi, Edukasi, SAD, KAT